Surface-modified calcium carbonate, preparation method and application of surface-modified calcium carbonate in high-performance antibacterial plastic
By preparing surface-modified calcium carbonate, using a modifier to make it hydrophobic and added to nylon 66, the problems of strong hygroscopicity and insufficient antibacteriality of nylon 66 are solved, and the performance and application fields of the material are significantly improved.
Patent Information
- Application Number
- CN202411345994.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-03
AI Technical Summary
Nylon 66 material has strong hygroscopicity in humid environments, resulting in bacteria and mold growth, and insufficient antibacterial performance. It is difficult for the prior art to effectively improve its hygroscopicity and antibacteriality.
Through the preparation method of surface-modified calcium carbonate, calcium carbonate is made hydrophobic by using modifiers such as stearic acid, silane coupling agent and titanate coupling agent, and added to nylon 66 to significantly reduce hygroscopicity And improve antibacterial properties.
It significantly reduces the hygroscopicity of nylon 66 and improves its antibacterial properties, expands the application field and improves economic benefits.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of calcium carbonate modification, and in particular to a surface-modified calcium carbonate, a preparation method and application thereof in high-performance antibacterial plastics. Background Art
[0002] Nylon 66, also known as polyamide 66 or PA66, is a high-performance polymer made by polycondensation reaction. It has the advantages of high mechanical strength, good heat resistance, wear resistance, self-lubrication, good chemical stability, etc. Nylon 66 is widely used in the fields of automobiles, electronic appliances, mechanical equipment, etc., and is often used to manufacture high-strength or wear-resistant parts such as gears, bearings, pump impellers, etc.
[0003] Nylon 66 has excellent physical and chemical properties, but it does not have obvious antibacterial properties. When used in complex or specific environments, such as humid or high humidity environments, it will cause the growth of bacteria and mold, which will affect the structure of the nylon 66 material, thereby affecting the performance and service life of nylon 66. In the prior art, adding antibacterial agents or performing surface modification can give nylon 66 antibacterial ability. For example, by doping with permanganate ions, nylon 66 fibers with high antibacterial properties can be prepared. This modified nylon 66 fiber shows significant antibacterial activity against Staphylococcus aureus and Candida albicans. Another method is to covalently bond the insecticidal cyclic N-chloramine part to nylon 66, and the resulting nylon 66 material has good antibacterial properties.
[0004] However, nylon 66 has strong hygroscopicity, mainly due to the amide groups (-CONH-) in its molecular structure. These amide groups can form hydrogen bonds with water molecules, thereby absorbing moisture, making nylon 66 easy to absorb moisture in a humid environment. This characteristic makes nylon 66 material more prone to the growth of bacteria or mold, while nylon 66 modified with antibacterial agents cannot improve the hygroscopicity of nylon 66, and its antibacterial performance is still insufficient in a humid environment.
[0005] Calcium carbonate is an inorganic compound with the chemical formula CaCO3, which consists of a calcium ion (Ca 2+ ) and a carbonate ion (CO3 2- ) It is usually white crystals, odorless, basically insoluble in water, but can be dissolved under acidic conditions and release carbon dioxide gas. Calcium carbonate is widely present in nature, such as the main component of limestone, marble, etc. In addition, it is also the main component of some animal bones or shells. In industry, calcium carbonate has a wide range of applications, such as in papermaking, metallurgy, glass, alkali production, rubber, medicine, pigments, organic chemicals, etc.
[0006] Adding calcium carbonate to nylon 66 can improve its hygroscopic properties to a certain extent. As a filler, calcium carbonate can reduce the water absorption of nylon 66 and improve its stability. However, simply adding calcium carbonate can only play the role of filler, and has a poor effect on improving the hygroscopic properties of nylon 66, and thus cannot significantly improve the antibacterial properties of nylon 66. Summary of the invention
[0007] The purpose of the present invention is to provide a surface-modified calcium carbonate, a preparation method and its application in high-performance antibacterial plastics, which can solve the technical problems in the prior art that nylon 66 plastic has strong hygroscopicity, poor antibacterial property and narrow application field.
[0008] To achieve the above object, the present invention adopts the following technical solutions:
[0009] A surface-modified calcium carbonate is prepared from the following raw materials in parts by weight: 80-120 parts of 2000-mesh heavy calcium carbonate, 100-200 parts of anhydrous ethanol, 3-8 parts of a first modifier, 1-5 parts of a second modifier, 1-3 parts of a third modifier, 200-400 parts of toluene, 0.5-1 parts of a dispersant, and 0.1-0.2 parts of a stabilizer. Calcium carbonate provides basic physical and chemical properties, and the 2000-mesh heavy calcium carbonate prepared can have a larger specific surface area, which is conducive to the uniform distribution and reaction of the modifier, and can be better dispersed in a nylon 66 matrix; the first modifier, the second modifier, and the third modifier are used to modify the 2000-mesh heavy calcium carbonate, so that the 2000-mesh heavy calcium carbonate has good hydrophobicity, so that the 2000-mesh heavy calcium carbonate is added to nylon 66, and the hygroscopicity of nylon 66 is significantly reduced.
[0010] Furthermore, the first modifier is stearic acid; the second modifier is a silane coupling agent; and the third modifier is a titanate coupling agent. The long-chain alkyl part of stearic acid forms a hydrophobic film on the surface of calcium carbonate, which changes the surface of calcium carbonate particles from hydrophilic to hydrophobic, and can form a hydrophobic film on the surface of calcium carbonate, reducing the hygroscopicity of 2000-mesh heavy calcium carbonate; the silane coupling agent contains a functional group that can react with inorganic materials and a functional group that can react with organic polymers, and condenses with the hydroxyl groups on the surface of calcium carbonate to form a silicon oxygen bond (Si-O-Ca), which can enhance the compatibility of 2000-mesh heavy calcium carbonate with organic polymers; the alkoxy group (-OR) in the titanate coupling agent chemically reacts with the hydroxyl groups on the surface of calcium carbonate, and at the same time forms a hydrophobic layer on the surface of calcium carbonate, further enhancing the hydrophobicity and compatibility of 2000-mesh heavy calcium carbonate.
[0011] Furthermore, the silane coupling agent is vinyl triethoxysilane; the titanate coupling agent is diisopropyl di(acetylacetonate); vinyl triethoxysilane (Vinyltriethoxysilane, VTES) has a vinyl group (-CH=CH2) and three ethoxy groups (-OCH2CH3), wherein the vinyl group can copolymerize with the double bonds or other reactive groups in the organic polymer to enhance the binding force with the polymer matrix, and the ethoxy group can hydrolyze in the presence of water to form silanol (Si-OH), and then condense with the hydroxyl group (-OH) on the surface of calcium carbonate to form a stable silicon oxygen bond (Si-O-Ca). By forming a silicon oxygen bond, the silane coupling agent can firmly fix the calcium carbonate particles in the polymer matrix, thereby improving its dispersibility and compatibility in nylon 66; diisopropyl di(acetylacetonate) titanate (Diisopropyl Bis(acetylacetonate)titanate) has two acetylacetonate groups (-C5H7O2) and two isopropoxy groups (-OCH(CH3)2). The acetylacetonate groups can react with the hydroxyl groups on the surface of calcium carbonate to further enhance the hydrophobicity of calcium carbonate. The isopropoxy groups can react with the groups in organic polymers to enhance the compatibility of calcium carbonate with the polymer matrix. The hydrophobic layer formed on the surface of calcium carbonate can effectively reduce the hygroscopicity of calcium carbonate and improve the overall performance of nylon 66.
[0012] Furthermore, the dispersant is polyethylene glycol or polyvinyl alcohol, which improves the dispersibility of 2000-mesh heavy calcium carbonate in the solution and prevents particle agglomeration.
[0013] Furthermore, the stabilizer is BHT, which prevents side reactions during the modification process and stabilizes the final product.
[0014] A method for preparing surface-modified calcium carbonate comprises the following steps:
[0015] S1: Place 2000 mesh heavy calcium carbonate in a reactor, add anhydrous ethanol to dissolve the first modifier, then add a dispersant, stir and heat from room temperature to 60-80°C, keep the reaction for a certain time, and after the reaction is completed, take out, filter and dry;
[0016] S2: Place the 2000-mesh heavy calcium carbonate dried in S1 in a reactor, add a certain amount of toluene to dissolve it, slowly add the second modifier after dissolution, stir and heat from room temperature to 100-120°C, keep the reaction for a certain period of time, take out and filter, wash several times, remove excess toluene, and dry;
[0017] S3: Place the 2000-mesh heavy calcium carbonate dried in S2 in a reactor, add the remaining toluene to dissolve it, add the third modifier and stabilizer after dissolution, stir and heat from room temperature to 60-80°C, keep the reaction for a certain time, take out and filter, wash several times, remove excess toluene, and dry to obtain surface-modified calcium carbonate.
[0018] Furthermore, in the step S1, the reaction is maintained for 0.5-1 h; in the step S2, the reaction is maintained for 2-3 h; and in the step S3, the reaction is maintained for 1-1.5 h.
[0019] Furthermore, in step S2, the amount of toluene added is 1 / 2-2 / 3 of the total mass of toluene.
[0020] The invention discloses an application of surface-modified calcium carbonate in high-performance antibacterial plastics. The surface-modified calcium carbonate is mixed with raw materials including nylon 66 to obtain modified nylon 66, and then the modified nylon 66 is doped with antibacterial ions to obtain high-performance antibacterial plastics.
[0021] Furthermore, the antibacterial ions include permanganate ions.
[0022] Further, the preparation method of the modified nylon 66 is:
[0023] S1: mixing adipic acid and hexamethylenediamine in a 1:1 molar ratio to form nylon 66 salt;
[0024] S2: Prepare nylon 66 salt into an aqueous solution, and evenly disperse the modified 2000-mesh heavy calcium carbonate in the nylon 66 salt solution;
[0025] S3: subjecting a nylon 66 salt solution containing 2000 mesh heavy calcium carbonate to a polycondensation reaction to obtain modified nylon 66.
[0026] Furthermore, the preparation method of the high-performance antibacterial plastic is:
[0027] S1: 2-(dimethylamino)ethyl methacrylate was grafted onto modified nylon 66 by radiation-induced polymerization;
[0028] S2: soaking the modified nylon 66 after graft polymerization in a hydrogen bromide solution for protonation;
[0029] S3: The protonated modified nylon 66 is immersed in a high-temperature potassium manganate solution to obtain a high-performance antibacterial plastic through anion exchange.
[0030] The beneficial effects of the technology of the present invention compared with the prior art are as follows:
[0031] 1. The present invention modifies 2000-mesh heavy calcium carbonate by using a first modifier, a second modifier, and a third modifier to obtain surface-modified calcium carbonate, so that the calcium carbonate has good hydrophobicity, and the surface-modified calcium carbonate is added to nylon 66, which can significantly improve the hygroscopicity of nylon 66, improve the performance of nylon 66, and improve the application field and economic benefits.
[0032] 2. Among the first modifier, the second modifier and the third modifier of the present invention, the first modifier is stearic acid, the second modifier is a silane coupling agent, and the third modifier is a phthalate coupling agent. Stearic acid is a long-chain fatty acid. The long-chain alkyl part (lipophilic group) of stearic acid forms a hydrophobic film on the surface of calcium carbonate, so that the surface of calcium carbonate particles changes from hydrophilic to hydrophobic; one end of the titanium molecule of the titanate coupling agent reacts with the inorganic material, and the other end reacts with the organic polymer. When reacting with calcium carbonate, the alkoxy group (-OR) in the titanate coupling agent chemically reacts with the hydroxyl group on the surface of calcium carbonate to form a titanium oxygen bond (Ti-O-Ca), further enhancing the hydrophobicity and fixing the coupling agent on the surface of calcium carbonate; and the organic part of the titanate coupling agent Hein forms a hydrophobic layer on the surface of calcium carbonate to reduce the hygroscopicity of calcium carbonate; silane coupling agents usually contain a functional group that can react with inorganic materials and a functional group that can react with organic polymers. The silane coupling agent reacts with calcium carbonate and undergoes a condensation reaction with the hydroxyl groups on the surface of calcium carbonate to form a silicon-oxygen bond (Si-O-Ca), which can firmly fix the silane coupling agent on the surface of calcium carbonate. The organic functional group part of the silane coupling agent is compatible with the polymer matrix, which improves the dispersibility and compatibility of calcium carbonate in nylon polymers, so that the modified calcium carbonate can better bond with the nylon 66 interface; the hydrophobic film of stearic acid can reduce the polarity of the calcium carbonate surface, improve the adhesion effect of phthalate coupling agents and silane coupling agents, and form a more stable interface structure. Therefore, the modification of calcium carbonate with stearic acid, silane coupling agent and titanate coupling agent can not only improve the hydrophobicity of calcium carbonate, but also improve the compatibility of calcium carbonate in the nylon 66 matrix, so that the hydrophobic modified calcium carbonate can better combine with nylon 66, thereby improving the hygroscopicity of nylon 66. The three work together to synergistically reduce the hygroscopicity of nylon 66 and improve the performance of nylon 66.
[0033] 3. The present application modifies nylon 66 by adding surface-modified calcium carbonate to the nylon 66, which can inhibit the breeding and growth of bacteria, thereby significantly improving the antibacterial properties of the obtained plastic and further improving the application areas of nylon 66. DETAILED DESCRIPTION
[0034] Before further describing the specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terms used in the examples of the present invention are for describing specific embodiments rather than for limiting the scope of protection of the present invention.
[0035] A surface-modified calcium carbonate is prepared from the following raw materials in parts by weight: 80-120 parts of 2000-mesh heavy calcium carbonate, 100-200 parts of anhydrous ethanol, 3-8 parts of stearic acid, 1-5 parts of vinyl triethoxysilane, 1-3 parts of di(acetylacetonato) diisopropyl titanate, 200-400 parts of toluene, 0.5-1 parts of a dispersant, and 0.1-0.2 parts of a BHT stabilizer.
[0036] The dispersant is polyethylene glycol or polyvinyl alcohol.
[0037] A method for preparing surface-modified calcium carbonate comprises the following steps:
[0038] S1: Place 2000 mesh heavy calcium carbonate in a reactor, add stearic acid dissolved in anhydrous ethanol, and then add a dispersant, stir and heat from room temperature to 60-80°C, keep the reaction for 0.5-1h, and after the reaction is completed, take out, filter and dry;
[0039] S2: Place the 2000-mesh heavy calcium carbonate dried in S1 in a reactor, add 1 / 2-2 / 3 of the total mass of toluene to dissolve it, slowly add vinyl triethoxysilane after dissolution, stir and heat from room temperature to 100-120°C, keep the reaction for 2-3 hours, take out and filter, wash several times, remove excess toluene, and dry;
[0040] S3: Place the 2000-mesh heavy calcium carbonate dried in S2 in a reactor, add the remaining toluene to dissolve it, add di(acetylacetonato)titanate diisopropyl and BHT stabilizer after dissolution, stir and heat from room temperature to 60-80°C, keep the reaction for 1-1.5 hours, take out and filter, wash several times, remove excess toluene, and dry to obtain surface-modified calcium carbonate.
[0041] Technical principle for preparing surface modified calcium carbonate:
[0042] (I) Specific role and synergistic mechanism of raw materials
[0043] 1.2000 mesh heavy calcium carbonate: As the base material, its high mesh number ensures the fineness and uniformity of the particles, providing a good surface area for subsequent modification treatment, so that the modifier can attach and play a role more effectively. The high surface area not only increases the binding sites of the modifier, but also promotes the uniform distribution of the modification effect.
[0044] 2. Anhydrous ethanol: As a solvent, anhydrous ethanol helps dissolve the first modifier stearic acid in the first step, promoting its initial contact and reaction with the surface of calcium carbonate particles. Ethanol has moderate volatility, which helps to quickly remove the solvent in the subsequent drying process to avoid residual effects on product performance.
[0045] 3. The first modifier, stearic acid: As a long-chain fatty acid, the long-chain alkyl part of stearic acid can form a hydrophobic film on the surface of calcium carbonate, which changes the surface of calcium carbonate particles from hydrophilic to hydrophobic, and initially gives it hydrophobic properties. At the same time, the introduction of stearic acid molecular chains also provides more binding sites for subsequent modifiers, enhancing the hierarchy and durability of the modification effect.
[0046] 4. The second modifier silane coupling agent (vinyl triethoxysilane): In the second step, the silane coupling agent contains a functional group that can react with inorganic materials and a functional group that can react with organic polymers, which undergoes a condensation reaction with the hydroxyl groups on the surface of calcium carbonate to form silicon oxygen bonds (Si-O-Ca), which can enhance the compatibility of calcium carbonate with organic polymers; the introduction of vinyl triethoxysilane not only enhances the hydrophobic effect, but also produces good compatibility with subsequent modifiers through its organic functional groups, thereby promoting the synergistic effect between the modifiers.
[0047] 5. The third modifier titanate coupling agent (diisopropyl di(acetylacetonate) titanate): In the third step, the alkoxy group (-OR) of the titanate coupling agent reacts chemically with the hydroxyl group on the surface of calcium carbonate to form a hydrophobic layer on the surface of calcium carbonate, further enhancing the hydrophobicity and compatibility of nano calcium carbonate. It can not only form a complementary effect with the silane coupling agent, but also produce a stronger interaction with the polymer matrix through its multi-functional characteristics, broadening the application field of modified calcium carbonate.
[0048] 6. Toluene: As a solvent in the second and third steps, toluene not only helps dissolve the modifier, but also ensures the smooth progress of the modification process and the efficient completion of subsequent drying through its good solubility and volatility.
[0049] 7. Dispersant (polyethylene glycol or polyvinyl alcohol): added in the early stage of modification, it helps to prevent the agglomeration of calcium carbonate particles and improve the uniform distribution of the modifier on the particle surface, thereby optimizing the modification effect.
[0050] 8. Stabilizer BHT: BHT prevents side reactions during the modification process and stabilizes the final product.
[0051] (II) Raw material dosage control and process optimization
[0052] Controlling the amount of each raw material is the key to ensuring the modification effect. Too much or too little modifier may affect the formation and performance of the modified layer. For example, insufficient amount of stearic acid will result in a weak hydrophobic effect, while excessive amount may cause agglomeration between particles. Similarly, the precise ratio of silane coupling agent and titanate coupling agent is also a prerequisite for achieving the best synergistic effect.
[0053] In addition, the non-interchangeability of the preparation steps and the optimization of process parameters are equally important. Each step is designed for a specific modification target, such as initial modification by stearic acid, and then sequentially introducing silane coupling agents and titanate coupling agents for deep modification. This sequence ensures the progressive and maximized modification effect. At the same time, strict control of process parameters such as reaction temperature and time can accurately control the progress of the modification reaction and the quality of the product, thereby achieving unexpected technical effects.
[0054] In summary, the preparation of surface-modified calcium carbonate is a complex and delicate process, which integrates knowledge and technology from multiple fields such as materials science and chemical engineering. By deeply understanding the mechanism of action of each raw material and their synergistic effects, and strictly controlling the amount of raw materials and process parameters, the present invention is able to prepare surface-modified calcium carbonate products with excellent performance and wide application, bringing significant technological progress to the development of related industries.
[0055] The invention discloses an application of surface-modified calcium carbonate in high-performance antibacterial plastics. The surface-modified calcium carbonate is mixed with raw materials including nylon 66 to obtain modified nylon 66, and then the modified nylon 66 is doped with permanganate ions to obtain high-performance antibacterial plastics.
[0056] The following is a more specific example.
[0057] Example 1
[0058] A surface-modified calcium carbonate is prepared from the following raw materials in parts by weight: 100 parts of 2000-mesh heavy calcium carbonate, 180 parts of anhydrous ethanol, 6 parts of stearic acid, 5 parts of vinyl triethoxysilane, 2 parts of di(acetylacetonato) diisopropyl titanate, 350 parts of toluene, 0.8 parts of a dispersant, and 0.2 parts of a BHT stabilizer.
[0059] The dispersant is polyethylene glycol or polyvinyl alcohol.
[0060] A method for preparing surface-modified calcium carbonate comprises the following steps:
[0061] S1: Place 2000 mesh heavy calcium carbonate in a reactor, add stearic acid dissolved in anhydrous ethanol, then add a dispersant, stir and heat from room temperature to 65°C, keep the reaction for 1 hour, and after the reaction is completed, take out, filter and dry;
[0062] S2: Place the 2000-mesh heavy calcium carbonate dried in S1 in a reactor, add 1 / 2 of the total mass of toluene to dissolve it, slowly add vinyl triethoxysilane after dissolution, stir and heat from room temperature to 120°C, keep the reaction for 2.2 hours, take out and filter, wash several times to remove excess toluene, and dry;
[0063] S3: Place the 2000-mesh heavy calcium carbonate dried in S2 in a reactor, add the remaining toluene to dissolve it, add di(acetylacetonato)titanate diisopropyl and BHT stabilizer after dissolution, stir and heat from room temperature to 80°C, keep the reaction for 1.5 hours, take out and filter, wash several times, remove excess toluene, and dry to obtain surface-modified calcium carbonate.
[0064] The invention discloses an application of surface-modified calcium carbonate in high-performance antibacterial plastics. The surface-modified calcium carbonate is mixed with raw materials including nylon 66 to obtain modified nylon 66, and then the modified nylon 66 is doped with permanganate ions to obtain high-performance antibacterial plastics.
[0065] The preparation method of the modified nylon 66 is:
[0066] S1: mixing adipic acid and hexamethylenediamine in a 1:1 molar ratio to form nylon 66 salt;
[0067] S2: Prepare nylon 66 salt into an aqueous solution, and evenly disperse the modified 2000-mesh heavy calcium carbonate in the nylon 66 salt solution;
[0068] S3: subjecting a nylon 66 salt solution containing 2000 mesh heavy calcium carbonate to a polycondensation reaction to obtain modified nylon 66.
[0069] The preparation method of the high-performance antibacterial plastic is as follows:
[0070] S1: 2-(dimethylamino)ethyl methacrylate was grafted onto modified nylon 66 by radiation-induced polymerization;
[0071] S2: soaking the modified nylon 66 after graft polymerization in a hydrogen bromide solution for protonation;
[0072] S3: The protonated modified nylon 66 is immersed in a high-temperature potassium manganate solution to obtain a high-performance antibacterial plastic through anion exchange.
[0073] Example 2
[0074] A surface-modified calcium carbonate is prepared from the following raw materials in parts by weight: 80 parts of 2000-mesh heavy calcium carbonate, 150 parts of anhydrous ethanol, 3 parts of stearic acid, 2 parts of vinyl triethoxysilane, 1 part of di(acetylacetonato) diisopropyl titanate, 240 parts of toluene, 0.5 parts of a dispersant, and 0.1 parts of a BHT stabilizer.
[0075] The dispersant is polyethylene glycol or polyvinyl alcohol.
[0076] A method for preparing surface-modified calcium carbonate comprises the following steps:
[0077] S1: Place 2000 mesh heavy calcium carbonate in a reactor, add stearic acid dissolved in anhydrous ethanol, then add a dispersant, stir and heat from room temperature to 80°C, keep the reaction for 1 hour, and after the reaction is completed, take out, filter and dry;
[0078] S2: Place the 2000-mesh heavy calcium carbonate dried in S1 in a reactor, add 2 / 3 of the total mass of toluene to dissolve it, slowly add vinyl triethoxysilane after dissolution, stir and heat from room temperature to 110°C, keep the reaction for 2.5 hours, take out and filter, wash several times to remove excess toluene, and dry;
[0079] S3: Place the 2000-mesh heavy calcium carbonate dried in S2 in a reactor, add the remaining toluene to dissolve it, add di(acetylacetonato)titanate diisopropyl and BHT stabilizer after dissolution, stir and heat from room temperature to 75°C, keep the reaction for 1.2 hours, take out and filter, wash several times, remove excess toluene, and dry to obtain surface-modified calcium carbonate.
[0080] The invention discloses an application of surface-modified calcium carbonate in high-performance antibacterial plastics. The surface-modified calcium carbonate is mixed with raw materials including nylon 66 to obtain modified nylon 66, and then the modified nylon 66 is doped with permanganate ions to obtain high-performance antibacterial plastics.
[0081] The preparation method of the modified nylon 66 is:
[0082] S1: mixing adipic acid and hexamethylenediamine in a 1:1 molar ratio to form nylon 66 salt;
[0083] S2: Prepare nylon 66 salt into an aqueous solution, and evenly disperse the modified 2000-mesh heavy calcium carbonate in the nylon 66 salt solution;
[0084] S3: subjecting a nylon 66 salt solution containing 2000 mesh heavy calcium carbonate to a polycondensation reaction to obtain modified nylon 66.
[0085] The preparation method of the high-performance antibacterial plastic is as follows:
[0086] S1: 2-(dimethylamino)ethyl methacrylate was grafted onto modified nylon 66 by radiation-induced polymerization;
[0087] S2: soaking the modified nylon 66 after graft polymerization in a hydrogen bromide solution for protonation;
[0088] S3: The protonated modified nylon 66 is immersed in a high-temperature potassium manganate solution to obtain a high-performance antibacterial plastic through anion exchange.
[0089] Example 3
[0090] A surface-modified calcium carbonate is prepared from the following raw materials in parts by weight: 120 parts of 2000-mesh heavy calcium carbonate, 100 parts of anhydrous ethanol, 5 parts of stearic acid, 1 part of vinyl triethoxysilane, 2 parts of di(acetylacetonato) diisopropyl titanate, 400 parts of toluene, 1 part of a dispersant, and 0.1 part of a BHT stabilizer.
[0091] The dispersant is polyethylene glycol or polyvinyl alcohol.
[0092] A method for preparing surface-modified calcium carbonate comprises the following steps:
[0093] S1: Place 2000 mesh heavy calcium carbonate in a reactor, add stearic acid dissolved in anhydrous ethanol, then add a dispersant, stir and heat from room temperature to 70°C, keep the reaction for 0.5h, and after the reaction is completed, take out, filter and dry;
[0094] S2: Place the 2000-mesh heavy calcium carbonate dried in S1 in a reactor, add 2 / 3 of the total mass of toluene to dissolve it, slowly add vinyltriethoxysilane after dissolution, stir and heat from room temperature to 100°C, keep the reaction for 2 hours, take out and filter, wash several times, remove excess toluene, and dry;
[0095] S3: Place the 2000-mesh heavy calcium carbonate dried in S2 in a reactor, add the remaining toluene to dissolve it, add di(acetylacetonato)titanate diisopropyl and BHT stabilizer after dissolution, stir and heat from room temperature to 60°C, keep the reaction for 1 hour, take out and filter, wash several times, remove excess toluene, and dry to obtain surface-modified calcium carbonate.
[0096] The invention discloses an application of surface-modified calcium carbonate in high-performance antibacterial plastics. The surface-modified calcium carbonate is mixed with raw materials including nylon 66 to obtain modified nylon 66, and then the modified nylon 66 is doped with permanganate ions to obtain high-performance antibacterial plastics.
[0097] The preparation method of the modified nylon 66 is:
[0098] S1: mixing adipic acid and hexamethylenediamine in a 1:1 molar ratio to form nylon 66 salt;
[0099] S2: Prepare nylon 66 salt into an aqueous solution, and evenly disperse the modified 2000-mesh heavy calcium carbonate in the nylon 66 salt solution;
[0100] S3: subjecting a nylon 66 salt solution containing 2000 mesh heavy calcium carbonate to a polycondensation reaction to obtain modified nylon 66.
[0101] The preparation method of the high-performance antibacterial plastic is as follows:
[0102] S1: 2-(dimethylamino)ethyl methacrylate was grafted onto modified nylon 66 by radiation-induced polymerization;
[0103] S2: soaking the modified nylon 66 after graft polymerization in a hydrogen bromide solution for protonation;
[0104] S3: The protonated modified nylon 66 is immersed in a high-temperature potassium manganate solution to obtain a high-performance antibacterial plastic through anion exchange.
[0105] Example 4
[0106] A surface-modified calcium carbonate is prepared from the following raw materials in parts by weight: 90 parts of 2000-mesh heavy calcium carbonate, 120 parts of anhydrous ethanol, 8 parts of stearic acid, 4 parts of vinyl triethoxysilane, 3 parts of di(acetylacetonato) diisopropyl titanate, 210 parts of toluene, 0.5 parts of a dispersant, and 0.1 parts of a BHT stabilizer.
[0107] The dispersant is polyethylene glycol or polyvinyl alcohol.
[0108] A method for preparing surface-modified calcium carbonate comprises the following steps:
[0109] S1: Place 2000 mesh heavy calcium carbonate in a reactor, add stearic acid dissolved in anhydrous ethanol, then add a dispersant, stir and heat from room temperature to 60°C, keep the reaction for 0.8, and after the reaction is completed, take out, filter and dry;
[0110] S2: Place the 2000-mesh heavy calcium carbonate dried in S1 in a reactor, add 1 / 2 of the total mass of toluene to dissolve it, slowly add vinyltriethoxysilane after dissolution, stir and heat from room temperature to 120°C, keep reacting for 3 hours, take out and filter, wash several times to remove excess toluene, and dry;
[0111] S3: Place the 2000-mesh heavy calcium carbonate dried in S2 in a reactor, add the remaining toluene to dissolve it, add di(acetylacetonato)titanate diisopropyl and BHT stabilizer after dissolution, stir and heat from room temperature to 70°C, keep the reaction for 1.2 hours, take out and filter, wash several times, remove excess toluene, and dry to obtain surface-modified calcium carbonate.
[0112] The invention discloses an application of surface-modified calcium carbonate in high-performance antibacterial plastics. The surface-modified calcium carbonate is mixed with raw materials including nylon 66 to obtain modified nylon 66, and then the modified nylon 66 is doped with permanganate ions to obtain high-performance antibacterial plastics.
[0113] The preparation method of the modified nylon 66 is:
[0114] S1: mixing adipic acid and hexamethylenediamine in a 1:1 molar ratio to form nylon 66 salt;
[0115] S2: Prepare nylon 66 salt into an aqueous solution, and evenly disperse the modified 2000-mesh heavy calcium carbonate in the nylon 66 salt solution;
[0116] S3: subjecting a nylon 66 salt solution containing 2000 mesh heavy calcium carbonate to a polycondensation reaction to obtain modified nylon 66.
[0117] The preparation method of the high-performance antibacterial plastic is as follows:
[0118] S1: 2-(dimethylamino)ethyl methacrylate was grafted onto modified nylon 66 by radiation-induced polymerization;
[0119] S2: soaking the modified nylon 66 after graft polymerization in a hydrogen bromide solution for protonation;
[0120] S3: The protonated modified nylon 66 is immersed in a high-temperature potassium manganate solution to obtain a high-performance antibacterial plastic through anion exchange.
[0121] Example 5
[0122] A surface-modified calcium carbonate is prepared from the following raw materials in parts by weight: 110 parts of 2000-mesh heavy calcium carbonate, 100 parts of anhydrous ethanol, 4 parts of stearic acid, 3 parts of vinyl triethoxysilane, 1 part of di(acetylacetonato) diisopropyl titanate, 200 parts of toluene, 1 part of a dispersant, and 0.2 parts of a BHT stabilizer.
[0123] The dispersant is polyethylene glycol or polyvinyl alcohol.
[0124] A method for preparing surface-modified calcium carbonate comprises the following steps:
[0125] S1: Place 2000 mesh heavy calcium carbonate in a reactor, add stearic acid dissolved in anhydrous ethanol, then add a dispersant, stir and heat from room temperature to 75°C, keep the reaction for 0.5h, and after the reaction is completed, take out, filter and dry;
[0126] S2: Place the 2000-mesh heavy calcium carbonate dried from S1 in a reactor, add 1 / 2 of the total mass of toluene to dissolve it, slowly add vinyltriethoxysilane after dissolution, stir and heat from room temperature to 100°C, keep the reaction for 2.8 hours, take out and filter, wash several times to remove excess toluene, and dry;
[0127] S3: Place the 2000-mesh heavy calcium carbonate dried in S2 in a reactor, add the remaining toluene to dissolve it, add di(acetylacetonato)titanate diisopropyl and BHT stabilizer after dissolution, stir and heat from room temperature to 65°C, keep the reaction for 1.5 hours, take out and filter, wash several times, remove excess toluene, and dry to obtain surface-modified calcium carbonate.
[0128] The invention discloses an application of surface-modified calcium carbonate in high-performance antibacterial plastics. The surface-modified calcium carbonate is mixed with raw materials including nylon 66 to obtain modified nylon 66, and then the modified nylon 66 is doped with permanganate ions to obtain high-performance antibacterial plastics.
[0129] The preparation method of the modified nylon 66 is:
[0130] S1: mixing adipic acid and hexamethylenediamine in a 1:1 molar ratio to form nylon 66 salt;
[0131] S2: Prepare nylon 66 salt into an aqueous solution, and evenly disperse the modified 2000-mesh heavy calcium carbonate in the nylon 66 salt solution;
[0132] S3: subjecting a nylon 66 salt solution containing 2000 mesh heavy calcium carbonate to a polycondensation reaction to obtain modified nylon 66.
[0133] The preparation method of the high-performance antibacterial plastic is as follows:
[0134] S1: 2-(dimethylamino)ethyl methacrylate was grafted onto modified nylon 66 by radiation-induced polymerization;
[0135] S2: soaking the modified nylon 66 after graft polymerization in a hydrogen bromide solution for protonation;
[0136] S3: The protonated modified nylon 66 is immersed in a high-temperature potassium manganate solution to obtain a high-performance antibacterial plastic through anion exchange.
[0137] Comparative Example 1
[0138] It is basically the same as Example 3, except that the calcium carbonate is not modified.
[0139] Comparative Example 2
[0140] It is basically the same as Comparative Example 1, except that only the first modifier is used for modification of the surface-modified calcium carbonate.
[0141] Comparative Example 3
[0142] It is basically the same as Comparative Example 1, except that only the second modifier is used for modification in the surface-modified calcium carbonate.
[0143] Comparative Example 4
[0144] It is basically the same as Comparative Example 1, except that only the third modifier is used for modification of the surface-modified calcium carbonate.
[0145] 1. Plastic hygroscopicity test
[0146] The plastics prepared in Examples 1-5 and Comparative Examples 1-4 were tested for saturated water absorption according to the method of "GB T 1034-2008 Standard for Determination of Water Absorption of Plastics - Test for Saturated Water Absorption": the samples were dried in a 50°C oven for 24 hours, cooled to 25°C in a dryer, and each sample was weighed to an accuracy of 0.1 mg (mass m1). The samples were placed in a container filled with distilled water, and the water temperature was controlled at 23°C. After soaking for 24 hours, the samples were taken out, and all the water on the surface of the samples was quickly wiped off with a clean dry cloth or filter paper, and each sample was weighed again; soaked for another 48 hours, and after 1 hour in each period, the samples were taken out of the water, the water on the surface was wiped off, and re-measured within 1 minute to an accuracy of 0.1 mg, and weighed again until the mass remained unchanged (mass m2); the saturated water absorption was calculated according to the following formula:
[0147] Saturated water absorption rate = (m2-m1) / m1×100%,
[0148] The results of Examples 1-5 and Comparative Examples 1-4 are recorded as shown in Table 1.
[0149] Table 1 Plastic saturated water absorption
[0150] project Saturated water absorption (%) Example 1 2.3 Example 2 1.7 Example 3 1.2 Example 4 1.8 Example 5 2.6 Comparative Example 1 7.3 Comparative Example 2 5.0 Comparative Example 3 5.7 Comparative Example 4 6.2
[0151] It can be seen from Table 1 that
[0152] (1) The saturated moisture absorption rates of the plastics prepared in Examples 1-5 of the present invention are 2.3%, 1.7%, 1.2%, 1.8% and 2.6%, respectively. It can be seen that the present invention can significantly reduce the hygroscopicity of the plastic and improve the durability of the plastic by modifying calcium carbonate and preparing the plastic from the modified calcium carbonate.
[0153] (2) The high-performance modified calcium carbonate in Comparative Examples 1-4 was not modified or not completely modified with the first modifier, the second modifier, and the third modifier of the present application, and the saturated moisture absorption performance was 7.3%, 5.0%, 5.7%, and 6.2%, respectively. It can be seen that in the present application, by adding calcium carbonate modified with the first modifier, the second modifier, and the third modifier, the moisture absorption performance of the plastic can be significantly improved, indicating that the first modifier, the second modifier, and the third modifier of the present invention can be used together to reduce the moisture absorption of the plastic and improve the performance of the plastic.
[0154] This is due to:
[0155] Stearic acid is a long-chain fatty acid. The long-chain alkyl part (lipophilic group) of stearic acid forms a hydrophobic film on the surface of calcium carbonate, which changes the surface of calcium carbonate particles from hydrophilic to hydrophobic. One end of the titanium molecule of the titanate coupling agent reacts with the inorganic material, and the other end reacts with the organic polymer. When reacting with calcium carbonate, the alkoxy group (-OR) in the titanate coupling agent reacts chemically with the hydroxyl group on the surface of calcium carbonate to form a titanium oxygen bond (Ti-O-Ca), further enhancing the hydrophobicity and fixing the coupling agent on the surface of calcium carbonate. The organic part of the titanate coupling agent forms a hydrophobic layer on the surface of calcium carbonate, reducing the hygroscopicity of calcium carbonate. The silane coupling agent generally It often contains a functional group that can react with inorganic materials and a functional group that can react with organic polymers. The silane coupling agent reacts with calcium carbonate and undergoes a condensation reaction with the hydroxyl groups on the surface of calcium carbonate to form a silicon-oxygen bond (Si-O-Ca), which can firmly fix the silane coupling agent on the surface of calcium carbonate. The organic functional group of the silane coupling agent is compatible with the polymer matrix, which improves the dispersibility and compatibility of calcium carbonate in nylon polymers, so that the modified calcium carbonate can better bond with the nylon 66 interface; the hydrophobic film of stearic acid can reduce the polarity of the calcium carbonate surface, improve the adhesion effect of phthalate coupling agents and silane coupling agents, and form a more stable interface structure. Therefore, modifying calcium carbonate with stearic acid, silane coupling agent, and titanate coupling agent can not only improve the hydrophobicity of calcium carbonate, but also improve the compatibility of calcium carbonate in the nylon 66 matrix, so that the hydrophobic modified calcium carbonate can better combine with nylon 66, thereby improving the hygroscopicity of the plastic. The three work together to synergistically reduce the hygroscopicity of the plastic and improve the performance of the plastic.
[0156] 2. Plastic antibacterial test
[0157] Escherichia coli and Staphylococcus aureus were selected and cultured on nutrient agar overnight, and the bacterial suspension was evenly coated on the nutrient agar plate. The plastic prepared in Example 3 and Comparative Examples 1-4 was placed on the inoculated agar plate and gently pressed to ensure good contact. The samples were cultured at 37°C for 72 hours, and the inhibition zone was observed to see whether it was formed around the samples, and the diameter of the inhibition zone was measured, and the antibacterial rate was calculated.
[0158] Table 2 Antibacterial properties of plastics
[0159] project Escherichia coli antibacterial rate (%) Staphylococcus aureus (%) Example 3 99.1 99.3 Comparative Example 1 75.2 78.0 Comparative Example 2 84.1 86.2 Comparative Example 3 81.4 83.5 Comparative Example 4 80.3 82.1
[0160] As can be seen from Table 2, the antibacterial rates of Example 3 against Escherichia coli and Staphylococcus aureus are 99.1% and 99.3%, respectively, while the antibacterial rates of Comparative Examples 1-4 against Escherichia coli are 75.2%, 84.1%, 81.4%, and 80.3%, respectively, and the antibacterial properties against Staphylococcus aureus are 78.0%, 86.2%, 83.5%, and 82.1%, respectively. The antibacterial properties of Comparative Examples 1-4 are much lower than those of the present application. It can be seen that the present application can significantly improve the antibacterial properties of the plastic and improve the application field of the plastic by adding surface-modified calcium carbonate to nylon 66 to prepare the modified plastic.
[0161] This is due to:
[0162] Surface-modified calcium carbonate added to nylon 66 can significantly improve the hygroscopicity of the resulting plastic, thereby inhibiting the breeding and growth of bacteria, and thus significantly improving the antibacterial properties of the resulting plastic.
[0163] The embodiments described above are only descriptions of the preferred methods of the technology of the present invention, and are not intended to limit the scope of the technology of the present invention. Without departing from the technical design spirit of the present invention, various modifications and improvements made to the technical scheme of the present invention by ordinary technicians in this field should fall within the protection scope determined by the technical claims of the present invention.
Claims
1. A surface-modified calcium carbonate, characterized in that: The invention comprises the following raw materials in parts by weight: 80-120 parts of 2000-mesh heavy calcium carbonate, 100-200 parts of anhydrous ethanol, 3-8 parts of a first modifier, 1-5 parts of a second modifier, 1-3 parts of a third modifier, 200-400 parts of toluene, 0.5-1 parts of a dispersant and 0.1-0.2 parts of a stabilizer.
2. A surface-modified calcium carbonate according to claim 1, characterized in that: The first modifier is stearic acid; the second modifier is a silane coupling agent; and the third modifier is a titanate coupling agent.
3. A surface-modified calcium carbonate according to claim 2, characterized in that: The silane coupling agent is vinyl triethoxysilane; the titanate coupling agent is di(acetylacetonato) diisopropyl titanate.
4. A surface-modified calcium carbonate according to claim 1, characterized in that: The dispersant is polyethylene glycol or polyvinyl alcohol.
5. A surface-modified calcium carbonate according to claim 1, characterized in that: The stabilizer is BHT.
6. A method for preparing a surface-modified calcium carbonate according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Place 2000 mesh heavy calcium carbonate in a reactor, add anhydrous ethanol to dissolve the first modifier, then add a dispersant, stir and heat from room temperature to 60-80°C, keep the reaction for a certain time, and after the reaction is completed, take out, filter and dry; S2: Place the 2000-mesh heavy calcium carbonate dried in S1 in a reactor, add a certain amount of toluene to dissolve it, slowly add the second modifier after dissolution, stir and heat from room temperature to 100-120°C, keep the reaction for a certain period of time, take out and filter, wash several times, remove excess toluene, and dry; S3: Place the 2000-mesh heavy calcium carbonate dried in S2 in a reactor, add the remaining toluene to dissolve it, add the third modifier and stabilizer after dissolution, stir and heat from room temperature to 60-80°C, keep the reaction for a certain time, take out and filter, wash several times, remove excess toluene, and dry to obtain surface-modified calcium carbonate.
7. The method for preparing a surface-modified calcium carbonate according to claim 6, characterized in that: In the step S1, the reaction is maintained for 0.5-1 h; in the step S2, the reaction is maintained for 2-3 h; in the step S3, the reaction is maintained for 1-1.5 h.
8. The method for preparing a surface-modified calcium carbonate according to claim 6, characterized in that: In the step S2, the amount of toluene added is 1 / 2-2 / 3 of the total mass of toluene.
9. Use of a surface-modified calcium carbonate according to any one of claims 1 to 5 in high-performance antibacterial plastics, characterized in that: The surface-modified calcium carbonate is mixed with raw materials including nylon 66 to obtain modified nylon 66, and then the modified nylon 66 is doped with antibacterial ions to obtain a high-performance antibacterial plastic.
10. The use of a surface-modified calcium carbonate in high-performance antibacterial plastics according to claim 9, characterized in that: The antibacterial ions include permanganate ions.
